Hubungan Kualitas Aset, Rasio Kecukupan Modal, dan Efisiensi Terhadap Tingkat Kesehatan Bank - Erawati, Teguh; Kariyah, Isbah Kul (Universitas Batanghari Jambi, 2024)
Banking institutions have influence on economic growth, so it must be ensured that banks are in a healthy condition. Lending that exceeds the maximum lending limit and only focuses on related businesses is the reason for the decline in bank health. This study aims to examine the relationship between asset quality, capital adequacy ratio, and efficiency to the soundness level of a bank. The data used in this study is secondary data in the form of financial statements of commercial banks listed on the IDX for 4 years from 2019-2022. The method used for sampling is purposive sampling method with a total population of 47 banks in the banking sector. The resulting sample is 64 data from 16 banks. The data analysis technique used in this study uses multiple linear regression techniques. The results of the regression test show that the capital adequacy ratio has no effect on the soundness of a bank, while asset quality and efficiency have a positive effect on the soundness of a bank.